(3CSGdjH GdJMdjd Gdcej (B:s (3eONd dOQGSI GdJShjb GdMOjK (B/s - (3GdfShQ, GjGO YHO GdaJGMs ((3YeGf(B: s (3OGQ UaGA(B, s, 2011)
(3ebOeI aj GdJMdjd Gdcej h feGPL GdGfMOGQ GdKfGFj , GdGfMOGQ GdeJYOO , GdefGgL GdcejI aj GdJSYjQ , GdJfHD HGdcdH , SdGSd eGQcha h GNJjGQ GdShb , feGPL fXQjI GdGfJXGQ , feGPL eTGcd Gdfbd h feGPL eTGcd GdJYjjf , bVGjG aj OQGSI Sdhc GdeSJgdc(B.s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdJMdjd Gdcejs; (3GdJShjbs